Pride and prejudice and pittsburgh ebook - Lippincott, Rachael (2023)
From the New York Times bestselling coauthor of Five Feet Apart and She Gets the Girl comes a fresh and inventive sapphic romantic comedy that's "a gem of a book" ( Booklist , starred review) "perfect for fans of Outlander and Bridgerton " ( Kirkus Reviews ). What if you found a once-in-a-lifetime love...just not in your lifetime? Audrey Cameron has lost her spark. But after getting dumped by her first love and waitlisted at her dream art school all in one week, she has no intention of putting her heart on the line again to get it back. So when local curmudgeon Mr. Montgomery walks into her family's Pittsburgh convenience store saying he can help her, Audrey doesn't know what she's expecting...but it's definitely not that she'll be transported back to 1812 to become a Regency romance heroine. Lucy Sinclair isn't expecting to find an oddly dressed girl claiming to be from two hundred years in the future on her family's estate. But she has to admit it's a welcome distraction from being courted by a man her father expects her to marry—who offers a future she couldn't be less interested in. Not that anyone has cared about what or who she's interested in since her mother died, taking Lucy's spark with her. While the two girls try to understand what's happening and how to send Audrey home, their sparks make a comeback in a most unexpected way. Because as they both try over and over to fall for their suitors and the happily-ever-afters everyone expects of them, they find instead they don't have to try at all to fall for each other. But can a most unexpected love story survive even more impossible circumstances?